Interseccionalidade e justiça social: um olhar no campo da Filosofia do Direito - Oliveira, Jennifer Aline Ernesto de (2023)
Identity is a set of characteristics that distinguish a person or thing and through which they can be individualized. In the political, social, legal, and economic context, various identities serve as markers of differences among individuals or social groups. Aspects of Identity are often perceived through the following factors: “age, gender, sexual orientation, religion, social class, ethnicity, race, language, nationality, geographical location, among others categories of analysis”. Considering the identity of Black women and the lack of response from the American legal system, black feminist Kimberlé Crenshaw coined the term Intersectionality in 1989 to name and investigate the injustices faced by Black women, which were not perceived within the category of women or the category of Blacks when seeking redress for the injustices they experienced. From this conceptualization, several intellectuals have been discussing the concept, which has generated numerous controversies regarding its complexity and purpose. Patrícia Hill Collins, for example, invites the scientific community to consider intersectionality as a social critical theory, aimed at achieving social justice. Therefore, through a historical and bibliographic construction, this work aims to investigate the origins of the concept and highlight some scientific contributions to the maturation of the concept/theory from a perspective of Philosophy of Law